Evaluation of mycotoxins and their metabolites in human breast milk using liquid chromatography coupled to high resolution mass spectrometry - Rubert, Josep; León, Nuria; Sáez, Carmen; Martins, Claudia P B; Godula, Michal; Yusà, Vicent; Mañes, Jordi; Soriano, José Miguel; Soler, Carla (Analytica chimica acta, 2014)
Humans can be exposed to mycotoxins through the food chain. Mycotoxins are mainly found as contaminants in food and could be subsequently excreted via biological fluids such as urine or human breast milk in native or metabolised form. Since breast milk is usually supposed as the only food for new-borns, the occurrence of mycotoxins in thirty-five human milk samples was evaluated by a newly developed method based on QuEChERS extraction and UHPLC-HRMS detection. The method described here allows the detection of target mycotoxins in order to determine the quality of this initial feeding. The method has been fully validated, with recoveries ranging from 64% to 93% and relative standard deviations (RSD, %) being lower than 20%. Using the method described, non-metabolised mycotoxins such as ZEA, NEO, NIV, ENA, ENA1, ENB, ENB1 and metabolites, such as ZEA metabolites, HT-2, DOM and T-2 triol were detected in human milk samples. Results obtained help to estimate the exposure of mothers and infants to mycotoxins. Moreover, to the best of our knowledge, this is the first work describing the simultaneous detection, quantification and screening of mycotoxins and their metabolites in human mature milk.
Keywords: Mycotoxins; Reproducibility of Results; reprodukovatelnost výsledků; těhotenství; Milk, Human; Chromatography, High Pressure Liquid; Mass Spectrometry; vysokoúčinná kapalinová chromatografie; kontaminace potravin; mykotoxiny; Infant, Newborn; Orbitrap; ženské pohlaví; novorozenec; mateřské mléko; Humans; Pregnancy; Human milk; Food Contamination; Sample preparation; Biomarkers; Female; Liquid chromatography–high resolution mass spectrometry; hmotnostní spektrometrie; lidé